Comparison of efficacy of Salmonella typhimurium A1-R and chemotherapy on stem-like and non-stem human pancreatic cancer cells - Hiroshima, Yukihiko (Landes Bioscience, 2013)
The XPA1 human pancreatic cancer cell line is dimorphic, with spindle stem-like cells and round non-stem cells. We report here the in vitro IC(50) values of stem-like and non-stem XPA1 human pancreatic cells cells for: (1) 5-fluorouracil (5-FU), (2) cisplatinum (CDDP), (3) gemcitabine (GEM), and (4) tumor-targeting Salmonella typhimurium A1-R (A1-R). IC(50) values of stem-like XPA1 cells were significantly higher than those of non-stem XPA1 cells for 5-FU (P = 0.007) and CDDP (P = 0.012). In contrast, there was no difference between the efficacy of A1-R on stem-like and non-stem XPA1 cells. In vivo, 5-FU and A1-R significantly reduced the tumor weight of non-stem XPA1 cells (5-FU; P = 0.028; A1-R; P = 0.011). In contrast, only A1-R significantly reduced tumor weight of stem-like XPA1 cells (P = 0.012). The combination A1-R with 5-FU improved the antitumor efficacy compared with 5-FU monotherapy on the stem-like cells (P = 0.004). The results of the present report indicate A1-R is a promising therapy for chemo-resistant pancreatic cancer stem-like cells.